Autocuidado del paciente hipertenso, según Dorothea Orem - Miguel Angel, Miguel Angel (2019)
Arterial Hypertension is considered one of the main diseases that causes morbidity and mortality worldwide, it is considered as a silent disease that affects millions of people regardless the gender, age, ethnicity and socioeconomic status established by the increase in the blood pressure values. This research work allowed us to describe the most relevant aspects of studies about hypertensive patient self-care, according to Dorothea Orem. A literature review was carried out by selecting 27 documents obtained from bibliographic bases such as Scielo, Redalyc, BVS and visits on official websites of the World Health Organization and the Ministry of Public Health of Ecuador, published along the years 2013 and 2019. After the corresponding Documentary analysis, we concluded that self-care actions based on the Dorothea Orem theory are performed by the hypertensive patient themselves daily with the aim of improving their quality of life, avoiding complications such as: strokes, heart failure, kidney chronic disease, among others. Self-care is defined as a deliberate action, based on the implicit assumption where human beings have free will to decide for a treatment